Pelaksanaan Fungsi Pengawasan DPRD Kota Denpasar Terhadap Pembangunan di Kota Denpasar - Anak Agung Bagus Brameswara Somanatha; I Gusti Bagus Suryawan; I Wayan Arthanaya (Warmadewa Press, 2024)
In carrying out the rhythm of regional government that goes hand in hand with the functions of the legislature, regional budgets and controls that are implemented, success is reflected in the Regional Government, with the DPRD as the pawn of the regional government, the regional functions are increasing with the existence of a regional executive body and also the Representative Council Area. The problems are 1). How is the Oversight Function Implementation of the Denpasar Municipal DPRD towards the sustainability of Development in the City of Denpasar? 2) What factors influence the oversight performance of the Denpasar City DPRD? By applying the empirical method in this study, the field facts became the basis of the research, with primary and secondary data which became a reference in the formation of research that was analyzed and studied to become a source of descriptive legal material when it was about to become a conclusion. The conclusions in the study, Implementation of the Supervisory function of the Denpasar Municipal DPRD for the sustainability of development in the City of Denpasar.